Defending against key exposure in attribute–based encryption. (16th October 2014) - Li, J.; Chen, X.; Tian, H.; Gao, C.
Since the notion of attribute–based encryption (ABE) was proposed, it has been found a lot of important applications such as fine–grained access control. However, the issue of key exposure problem in ABE has been solved completely. This problem is formally addressed and formulated in this paper. More specifically, we propose a new key–insulated ABE (KI–ABE) scheme as a solution to the key exposure problem. The definition and security model of KI–ABE is proposed. Then, a KI–ABE scheme is presented, which is provably secure under the proposed model. The scheme is secure in the remaining time periods against an adversary who compromises the insecure device and obtains secret keys for the periods of its choice. Finally, we show that the scheme also supports user delegation, which is critical when one wants to delegate part of attributes (privileges) to others.